PENGARUH PERUBAHAN IKLIM TERHADAP KETAHANAN PANGAN DI PROPINSI ACEH - Sufriadi, Sufriadi; Ringo, Liston Siringo; Handayani, Sri; Nasution, Aswin (JURNAL AGRIMANSION, 2025)
ABSTRACT Climate change poses a threat to food security and impacts food availability in the region, especially in Aceh Province. The decline in the district food crop production index during the 2016-2023 period indicates a disruption in the agricultural production system in most areas of Aceh Province. This study aims to analyse the effect of climate change on food security in Aceh Province in the short and long term with the Auto Regressive Distributed Lag (ARDL) model approach using panel data (21 district cross section data and time series from 2018-2023) variables of food security index, harvest area, district production obtained from the Central Bureau of Statistics (BPS) and the Regional Food Security Agency (BKPD) while climate data on temperature, rainfall and humidity obtained from the Aceh Province Meteorology and Geophysics Agency (BMKG). The results of the analysis show that the variability of temperature, rainfall and district production has a long-term relationship to the Aceh Food Security Index (IKPA) with a temperature coefficient = 7.583732, meaning that every 1% increase in temperature will cause an increase in IKPA by 7.5%, the rainfall coefficient = 12.63413 means that every 1% increase in rainfall will cause a decrease in IKPA by 12.6% and the coefficient of rice production = 60.30847 means that every 1% increase in rice production will cause an increase in IKPA by 60.3% and the coefficient of corn production = 0.973232 means that every 1% increase in rice production will cause an increase in IKPA by 60.3%. The coefficient of maize production=0.973232 means that every 1% increase in maize production will cause an increase in IKPA by 0.97%. The implication of this research is that a policy or adaptation strategy is needed against rainfall variability that is too high can cause an increase in the population of pests and diseases of rice plants to cause fuso and have an impact on food availability and food security of Aceh Province in the long term. Keywords: Climate change, Production, Food Security, Aceh